2019
DOI: 10.1097/ipc.0000000000000726
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Link Between Methicillin-Resistant Staphylococcus aureus Strains Isolated From 2 Different Cities in Iran

Abstract: Background Methicillin-resistant Staphylococcus aureus (MRSA) strains are known as one of the most important multidrug-resistant organisms causing infections in humans and animals. The objectives of this experimental study were to characterize the clonality and antibiotic resistance of MRSA strains isolated from patients in 2 different cities in Iran. Methods During 2 years, a total of 536 S. aureus isolates were collected from 2 reference hospitals in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
0
1
Order By: Relevance
“…CT1 was the dominant PhP type in this study, followed by CT2, CT4, and CT8. Compared to our previous studies [3,5,10,12,17,19,20] , it was found that certain clonal PhP types are disseminating and circulating in different regions in Tehran. Moreover, the presence of MRSA strains with different antibiotic resistance and prophage patterns in a certain PhP type in this study indicated independent evolution of such clones in the community.…”
Section: Discussioncontrasting
confidence: 76%
“…CT1 was the dominant PhP type in this study, followed by CT2, CT4, and CT8. Compared to our previous studies [3,5,10,12,17,19,20] , it was found that certain clonal PhP types are disseminating and circulating in different regions in Tehran. Moreover, the presence of MRSA strains with different antibiotic resistance and prophage patterns in a certain PhP type in this study indicated independent evolution of such clones in the community.…”
Section: Discussioncontrasting
confidence: 76%